(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the main factors that influenced the formation of Eastern classical pedagogical thought. Specifically, it provides a scholarly overview of the socio-historical conditions, religious and educational views, philosophical teachings, and the system of education and upbringing formed on the pedagogical legacy of great thinkers. Furthermore, the significance of Eastern pedagogical thought in the modern education system is explored.